The agricultural economies of early urban systems in the northern Fertile Crescent - Kim, H (2019)
Archaeobotanical investigation of Neolithic-Bronze Age sites in the northern Fertile Crescent has mostly focussed on the Neolithic-Chalcolithic and also on the Euphrates valley. The aim of this study is instead the Bronze Age, especially the later Bronze Age of the second millennium BC. The three sites studied, Tell Mohammed ‘Arab, Tell Brak and Tell Atchana, are distributed across the northern Fertile Crescent, in the Tigris, Khabur and Orontes valleys, respectively, and offer assemblages mostly dating to the Late Bronze Age. In conjunction with synthesis of previously published archaeobotanical data from the second millennium BC, this study contributes to a comprehensive overview of agriculture across the region, including its relationship with social complexity and climate change. The new data on crop spectra and associated arable weed/wild taxa is analysed using multivariate statistical approaches, ethnoarchaeological models, functional weed ecology and crop stable isotope analysis. The results reveal the major crop types used at each site, as well as pronounced regional variation in staple taxa; crop processing activities; and arable land management strategies. Overall, a strong correlation is observed among these different dimensions of agricultural activity, urbanisation cycles and scales and environmental settings.